Towards understanding the metabolism of in vitro Sutherlandia frutescens (L.)R.Br. cultures - Colling, Janine (Stellenbosch : University Stellenbosch, 2010)
Thesis (MSc (Plant Biotechnology))--University of Stellenbosch, 2009.